Modal and Focus Particles in Sign Languages. A Cross-Linguistic Study - Herrmann, Annika (Sign Languages and Deaf Communities [SLDC], 2014)
Bringing together the research fields of sign language linguistics and information structure, this bookfocuses onthe realization of modal particles and focus particles in three European sign languages: German Sign Language, Sign Language of the Netherlands, and Irish Sign Language. As a cross-linguistic investigation based on a systematic methodological approach, thestudy analyzes the results particularly with regard to nonmanual features expressed by articulators such as the body, head, and face. The analyses of the data provide interesting insights into the syntax-prosody interface in sign languages and the interaction of syntax and prosody in general. Modal and focus particles have not been thoroughly investigated in sign languages. This volumepresents the first studyon this phenomenonand is thus an innovative contribution to the field. From a methodological and theoretical perspective, it draws onup-to-date linguistic tools and provides professionally elicited and annotated data. The bookaccounts for theresultswithin existing theoretical models. Given its specific focus on nonmanuals, the book contributes to recent debates on information structure and the syntax-prosody interface and will be of special interest to both sign and spoken language linguists.